Pseudoexfoliation of the lens in Australian Aborigines. Issue 7 (July 1977) - Taylor, H. R.; Hollows, F. C.; Moran, D.
Abstract : The first cases of pseudoexfoliation of the lens to be found in Australian Aborigines are reported. The prevalence rate in the communities in central Australia is 1-3% and for those 61 years and older is 16-3%. Within the limits of our assessment glaucoma was an associated finding in 8-1% of these cases. A high incidence of old trachoma, previous trauma, and Labrador keratopathy was also noted in these people.